Amino acids utilisation by Clostridium difficile strains - Ogbu, H.I. (2016)
The carbon and energy metabolism of the human pathogen Clostridium difficile is poorly understood. Amino acid metabolism by the Stickland reactions has previously been described as a primary source of energy in a number of Clostridium species, especially when grown in a medium containing only amino acids. Deeper insights may be gained by metabolic analyses using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) platforms, but such experiments are best performed in well-defined growth media. A number of C. difficile strains have been successfully cultivated on defined media but these media provide an excess of nutrients, particularly in terms of amino acid provision, resulting in undesirable background growth in the absence of glucose. To overcome these challenges, three variants of a defined medium were developed that contain the essential nutrients that support the growth of this bacterium, in the presence of a carbon and energy source such as glucose together with an LC-MS/MS method that will simultaneously measure all twenty amino acids.